Assessment of Patients’ Compliance with Essential Hypertension - Alwey, samer (Iraqi National Journal of Nursing Specialties, 2008)
Objective:This study aims to asses the patients' compliance with essential hypertension in respect to antihypertensivemedications, follow-up, dietary pattern and health habits, to identify the associated long-term complications, andto find out the relationship between patient's compliance, and demographic characteristics such as age, gender,level of education, and duration of disease.Methodology:A descriptive study was carried out in Nasiriyah Teaching Hospital to achieve presented objectives .Results:The results of the study revealed that there were a significant association between educational level and totalpatient's compliance, a significant association was found between the duration of disease and complications, themajority (63%) of the sample was non-complaint, most of them was males with low level of education and(70%) of them had complications. A greater number (21%) suffering from (Cerebrovascular accident).Recommendation:The research recommends that establishing well-equipped specialized hypertension clinics, educational programshould be designed, antihypertensive drugs should be supported by government, antihypertensive medicationsmust be obtained from the out patient clinic to avoid buying them from private pharmacies to maintain patientscompliance, and further study can be conducted in Iraq to determine the impact of non-compliance of patientswith essential hypertension.